2020
DOI: 10.1007/s00468-020-01973-0
|View full text |Cite
|
Sign up to set email alerts
|

Growth and mortality of Norway spruce and European beech in monospecific and mixed-species stands under natural episodic and experimentally extended drought. Results of the KROOF throughfall exclusion experiment

Abstract: Key message Under severe drought, growth of Norway spruce suffered much more than European beech. Norway spruce benefited from growing in the environment of beech, and both species acclimated slightly to 5 years of experimentally extended drought. Abstract Recent studies show that the detrimental effects of drought on stand growth are mitigated when the stand contains mixed tree species. We analysed the growth responses of Norway spruce and European beech to episodic and experimentally extended drought in intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
75
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 99 publications
(82 citation statements)
references
References 55 publications
5
75
2
Order By: Relevance
“…This intersection between the courses of growth in mono-and mixed-species stands as a function of elevation was indicated by a significant (p < 0.05) interaction between the variables MixMono and elevation (see parameter a 12 , Table 4). The growth of beech in mountain forests accelerated in the last century, as in many lowland forests (Spiecker et al 2012;Pretzsch et al 2014aPretzsch et al , 2020a, due to climate change. In the lower mountain forests, the positive growth trends for beech were greater in monoculture than in mixture.…”
Section: Faster Growth Of Beech In Mixed Stands Versus Mono-specific mentioning
confidence: 99%
See 3 more Smart Citations
“…This intersection between the courses of growth in mono-and mixed-species stands as a function of elevation was indicated by a significant (p < 0.05) interaction between the variables MixMono and elevation (see parameter a 12 , Table 4). The growth of beech in mountain forests accelerated in the last century, as in many lowland forests (Spiecker et al 2012;Pretzsch et al 2014aPretzsch et al , 2020a, due to climate change. In the lower mountain forests, the positive growth trends for beech were greater in monoculture than in mixture.…”
Section: Faster Growth Of Beech In Mixed Stands Versus Mono-specific mentioning
confidence: 99%
“…However, there are also critical voices doubting the dominance of beech without humans due to an enhanced growth of beech since 1950 that can be primarily attributed to human influences like nitrogen fertilization or management effects (Scharnweber et al 2011(Scharnweber et al , 2019. Its dominance was reduced in the past for economic reasons, particularly in Central Europe, but its high mechanical stability against windthrow and comparatively high resistance and resilience to drought are leading to a comeback in view of climate change (Pretzsch et al 2020a;Paul et al 2019;Hanewinkel et al 2011). Presently beech forests cover about 12 × 10 6 ha in Europe (Brus et al 2012), and the area is steeply increasing due to a transition to close-to-nature forestry.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Resistance, resilience and recovery [21], as well as drought responses, of mixed and pure Norway Spruce (Picea abies [L.] Karst) and European Beech (Fagus sylvatica [L.]) have also been documented in studies recently [22][23][24]. Moreover, Pretzsch et al 2020 [25] reported spruce to be faster acclimated and by 20%-50% less affected within its interspecific neighborhood with beech, while the opposite was true for the beech. Neuner et al 2015 [26] report a higher survival probability of spruce in mixed stands with beech as compared to pure stands under warmer climate and poor soil conditions.…”
Section: Introductionmentioning
confidence: 98%